Contribution of K3 Implementation,the Role of Industrial Work Practice Mentoring and the Value of Productive Training Courses Towards Industrial Work Practice Results of Informatics Engineering Students Department Cokroaminoto Vocational School,Kotamobagu - Mamonto, Mutahir; Rompas, Parabelem Tinno Dolf; Olii, Djami; Oroh, Rolly Robert; Rotty, Viktory Nicodemus Joufree (International Journal of Information Technology and Education, 2023)
This research aims to determine the contribution of the implementation of K3, the role of industrial work practice supervisors, and the value of training courses on the results of industrial work practices both individually and collectively. The method used in this research is a quantitative method with data collection techniques used are questionnaires and documentation, while the data analysis technique used is multiple regression analysis with the help of SPSS 24. The results of the research show that there is a contribution from the application of occupational safety and health to the results of industrial practice among Informatics Engineering students at Cokroaminoto Vocational School. The contribution of the application of occupational safety and health to the results of industrial practice is 73.5%. There is a contribution from the role of industrial supervisor teachers to the results of industrial practice for Informatics Engineering students at Cokroaminoto Vocational School. The contribution of the role of industrial supervising teachers to the results of industrial practice is 72.6%. There is a contribution of the value of students' productive training courses to the results of industrial practice for students in the Informatics Engineering Department at Cokroaminoto Vocational School. The contribution of the role of industrial supervisors to the results of industrial practice is 74.4%. There is a contribution from the application of occupational safety and health, the role of industrial supervisors, and the value of students' productive training courses to the results of industrial practice together. The contribution of the application of occupational safety and health, the role of industrial supervisors, and the value of students' productive training courses to the results of industrial practice together is 75.3%, while the remainder is influenced by other variables that are not studied in this research.